2019
DOI: 10.1017/s000711451900309x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine promotes porcine type I muscle fibres formation through improvement of mitochondrial biogenesis

Abstract: The present study aimed to investigate whether arginine (Arg) promotes porcine type I muscle fibres formation via improving mitochondrial biogenesis. In the in vivo study, a total of sixty Duroc × Landrace × Yorkshire weaning piglets with an average body weight of 6·55 (sd 0·36) kg were randomly divided into four treatments and fed with a basal diet or a basal diet supplemented with 0·5, 1·0 and 1·5 % l-Arg, respectively, in a 4-week trial. Results showed that dietary supplementation of 1·0 % Arg significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…In addition, poor skeletal muscle performance is correlated with exercise fatigue ( Frisbee et al, 2019 ), which not only reduces the quality of life but also physical movement, worsening obesity and metabolic syndromes in offspring. In this study, we found that ME enhanced the oxidative capacity of offspring muscle by shifting muscle fiber types from glycolytic to oxidative without changing muscle weight, which might be associated with enhanced mitochondrial biogenesis ( Chen et al, 2020 ). Consistently, we found that ME improved the endurance capacity of offspring muscle.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, poor skeletal muscle performance is correlated with exercise fatigue ( Frisbee et al, 2019 ), which not only reduces the quality of life but also physical movement, worsening obesity and metabolic syndromes in offspring. In this study, we found that ME enhanced the oxidative capacity of offspring muscle by shifting muscle fiber types from glycolytic to oxidative without changing muscle weight, which might be associated with enhanced mitochondrial biogenesis ( Chen et al, 2020 ). Consistently, we found that ME improved the endurance capacity of offspring muscle.…”
Section: Discussionmentioning
confidence: 90%
“…Muscle fibers are divided into glycolytic and oxidative fibers, with oxidative fibers particularly rich in mitochondria and highly effcient in utilizing glucose and fatty acids [58]. It has been found that maternal exercise enhances the oxidative capacity of the progeny's muscles by changing the types of muscle fibers from glycolytic to oxidative without altering muscle mass, which may be associated with increased mitochondrial biogenesis [59].…”
Section: Mother's Physical Activitymentioning
confidence: 99%
“…It has been reported that the biogenesis of mitochondria can be strongly affected by nutrition. 7 The AMPK signaling pathway, as one of the nutrient-sensing pathways, regulates mitochondrial metabolism and biogenesis. 8 Additionally, the AMPK signaling pathway can also regulate the muscle fibertype composition, which can increase the slow muscle fiber level while reducing the fast muscle fiber level.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been reported that the biogenesis of mitochondria can be strongly affected by nutrition . The AMPK signaling pathway, as one of the nutrient-sensing pathways, regulates mitochondrial metabolism and biogenesis .…”
Section: Introductionmentioning
confidence: 99%